2009
DOI: 10.1249/mss.0b013e31819dfe14
|View full text |Cite
|
Sign up to set email alerts
|

Two Bouts of Exercise before Meals, but Not after Meals, Lower Fasting Blood Glucose

Abstract: These results demonstrate that exercise performed in postabsorptive, but not in postprandial state, lowers glucoregulatory set point and glucagon glycemic threshold and is accompanied by reduced vagal tone, counterregulatory responses, and glucagon glycemic threshold and by increased insulin-glucagon ratio. Reduced counterregulatory response, altered neuroendocrine function, and sustained lowering of blood glucose are most likely the consequences of reduced carbohydrate availability during exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…However, vigorous intensity is not always feasible at meal times; it often requires specialized equipment, is not desirable for all people, is precluded in the presence of some chronic conditions, and is initially inappropriate for inactive people [20]. Longer duration activity may also have been advantageous as studies of activity lasting for 2 h post-meal show improved glucose control [8]. Yet, for most people, 2 h of Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, vigorous intensity is not always feasible at meal times; it often requires specialized equipment, is not desirable for all people, is precluded in the presence of some chronic conditions, and is initially inappropriate for inactive people [20]. Longer duration activity may also have been advantageous as studies of activity lasting for 2 h post-meal show improved glucose control [8]. Yet, for most people, 2 h of Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2001, some studies [8,12,23,33,34,36,41,43] have highlighted the potential importance of activity-meal timing in relation to blood glucose control (reviewed in [39]). However, the number of studies is sparse and the sample sizes are small.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar exercise protocol in healthy, obese individuals demonstrated that 1-h of exercise (50% VO 2 max) increased plasma catecholamine concentrations and markers of lipid oxidation well into the recovery period (26). Furthermore, Borer et al (27) noted a 20% increase in glucose concentrations when glucose-tolerant, obese females performed 2-h of low-intensity walking (40–45% VO 2max ) an hour after a high-carbohydrate meal. Considering the lack of research examining the interaction between meal consumption and exercise on insulin secretion, substrate metabolism, and glucose excursions in obese individuals, we can only postulate that the meals used in the current study may have exacerbated the glucose excursions observed in the EX condition.…”
Section: Discussionmentioning
confidence: 99%
“…In response to the mental challenge in both conditions, elevations in HR, RPP, and CORT occurred, but when a mental stress was followed by a lowintensity exercise bout, an elevation of CORT was further demonstrated. Exercise of this low intensity is alone known not to be sufficient to stimulate cortisol release (Borer et al 2009;Davies and Few 1973;Hill et al 2008;Maresh et al 2006) and thus represents new findings regarding effects of mental stress on physical stress responses. Neither the mental challenge nor the exercise affected circulating catecholamines.…”
Section: Discussionmentioning
confidence: 99%